Differentiated Learning Approaches in Introvert and Extrovert Students from The Aspect of Personality Type in Vocational School Students - Noviantari, Ika; Rica, Rica (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2023)
The main objective of this research is to obtain data related to differentiated learning for introverted and extroverted students in vocational education/Vocational High Schools (SMK). The research carried out is a type of qualitative research with a case study approach. The data collection techniques used in this research were interviews and documentation. The questions will develop and be more open but still have the same focus. The interviews conducted in this research included interviews with 4 students as subjects chosen by students in class X of SMK Negeri 3 Tarakan. There were 4 participants in this research, namely 2 introverted students and 2 extroverted students, based on the considerations of guidance and counseling educators. The documentation used in this research is field note documents from guidance and counseling teachers as well as reports on the results of observations of the learning process. The Miles and Huberman model is used to analyze data with data reduction, data display, and conclusion drawing/verification analysis steps. The results of differentiated learning research must be adjusted to students' learning needs, especially students with introverted and extroverted personalities. Good activities and responsibilities can be used to design differentiated learning with a process and content approach. The product approach can also be used for students with introverted and extroverted personalities from the aspect of expressiveness. Meanwhile, the environmental approach can be applied to students with introverted and extroverted personalities by mapping the comfortable environment when studying and doing assignments individually or in groups. Keyword: differentiated learning, introvert, extrovert, Vocational High Schools